The effect of the use of recycled coarse aggregate on the performance of self-compacting concrete (SCC) and its application - Akhmad Suryadi (Eastern-European Journal of Enterprise Technologies, 2022)
The demand for self-compacting concrete is very high because this concrete has high flowability and has resistance to segregation. Natural aggregates are of high value, while concrete demolition materials are abundant and of low value. So that the recycled coarse aggregate can be used as concrete material, this study analyzes the characteristics of Self Compacting Concrete (SCC) using recycled coarse aggregate from construction waste. Tests for aggregate wear, aggregate hardness, compressive strength of concrete and tensile strength of concrete were carried out. The wear test refers to the standard AASHTO T-96-74, ASTM C-131-55 and SNI 2417-2008. This test uses recycled coarse aggregate that has been washed so that the sludge content is clean; after that, it was baked with the used aggregate, the aggregate that passed the 12.5 mm sieve and was retained in the 9.5 mm sieve. The test object is pressurized 40 tons at a speed of 4 tons/minute. Concrete Compressive Strength Test refers to SNI 03-1974-2011, using a scale with an accuracy of 0.3 % of the weight of the concrete, a concrete press machine and a capping machine. While the split tensile strength test of concrete refers to SNI 03-2491-2014, carried out on days 7, 21 and 28 with a cylindrical test object. Variations of recycled aggregates start from 0 %, 25 %, 50 %, 75 %, and 100 %. The design's compressive strength is 25 MPa. The results showed that the recycled aggregates had good gradation, high absorption and low specific gravity compared to natural aggregates. The recycled coarse aggregate reduces the compressive strength of the concrete and causes a decrease in a slump, thereby reducing the split tensile strength of the concrete